Low frequency aperture array developments for phase 1 SKA - Bij de Vaate, Jan; de Lera Acedo, E.; Virone, G.; Jiwani, Aziz; Razavi, N.; Perini, F.; Zarb-Adami, K.; Monari, J.; Padhi, Shantanu; Addamo, G.; Peverini, O.; Montebugnoli, S.; et al. (IEEE, 2011)
Aperture Arrays (AA) mark a new era in radio astronomy combining high sensitivity with a large field-of-view, enabling very high survey and imaging speeds. This paper describes the development of low frequency aperture arrays leading up to SKA phase 1 within the Aperture Array Verification Program (AAVP) as part of the SKA program.